2017
DOI: 10.1159/000481704
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Vitreous Hemorrhage from an Optic Nerve Retinal Arterial Macroaneurysm

Abstract: Objective: To report a case of recurrent vitreous hemorrhage from an optic nerve retinal arterial macroaneurysm (ONRAM) successfully treated with intraoperative endolaser. Patient and Methods: A 92-year-old woman on oral aspirin and warfarin anticoagulation for atrial fibrillation developed three episodes of dense vitreous hemorrhage from an ONRAM. Due to failure of the vitreous hemorrhage to clear spontaneously, a total of three pars plana vitrectomy (PPV) procedures were performed along with a 1.25-mg intrav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Treatment of RAMs is only required in symptomatic and complicated cases. Although some cases reported that laser photocoagulation for RAM on the optic disc was effective in symptomatic cases [ 11 , 13 ], the risk of visual field loss by this method should not be neglected. In this case, we did not observe any pulsation of the RAM or blood oozing from it intraoperatively, and the macula was intact.…”
Section: Discussion/conclusionmentioning
confidence: 99%
See 3 more Smart Citations
“…Treatment of RAMs is only required in symptomatic and complicated cases. Although some cases reported that laser photocoagulation for RAM on the optic disc was effective in symptomatic cases [ 11 , 13 ], the risk of visual field loss by this method should not be neglected. In this case, we did not observe any pulsation of the RAM or blood oozing from it intraoperatively, and the macula was intact.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…RAMs on the optic disc generally disappear without any intervention [ 6 , 14 , 15 ]. Although recurrent VH was not observed in this case, cases receiving oral anticoagulants should be monitored for the possibility of recurrence [ 6 , 11 ].…”
Section: Discussion/conclusionmentioning
confidence: 99%
See 2 more Smart Citations
“…1–3 Treatment with laser photocoagulation or vascular endothelial growth factor inhibitors is controversial, and it is reserved for persistent symptomatic cases. 4,5 The present photo essay exemplifies the typical evolution of these lesions through a multimodal approach.…”
mentioning
confidence: 93%